The Impact of Public Employment: Evidence from Bonn - Sascha O. Becker; Stephan Heblich; Daniel M. Sturm (Institute of Labor Economics (IZA), 2018)
This paper evaluates the impact of public employment on private sector activity using the relocation of the German federal government from Berlin to Bonn in the wake of the Second World War as a source of exogenous variation. To guide our empirical analysis, we develop a simple economic geography model in which public sector employment in a city can crowd out private employment through higher wages and house prices, but also generates potential productivity and amenity spillovers. We find that relative to a control group of cities, Bonn experiences a substantial increase in public employment. However, this results in only modest increases in private sector employment with each additional public sector job destroying around 0.2 jobs in industries and creating just over one additional job in other parts of the private sector. We show how this finding can be explained by our model and provide several pieces of evidence for the mechanisms emphasised by the model.
Keywords: F15; J45; N44; R12; 330; economic geography; public employment; place-based policies; German division